CURRENT TRENDS IN TESTAMENTARY SUCCESSION - Francois du Toit (Obiter, 2022)
In this article some current trends in testamentary succession are considered in order to establish a practice-based perspective re the rules of testamentary succession. The research was undertaken by means of the distribution of questionnaires to practitioners specialising in wills, trusts and deceased estates. The data received are hereby described and analysed.